Análise de placas duplas delgadas elasticamente conectadas: uma abordagem pelo método dos elementos de contorno - Pereira, Arthur Coutinho de Araújo (2020)
Investigations of elastically connected structures have been increased the interest of the scientific community, because these problems can be found in various branches of engineering such as civil, Aerospace and mechanical engineering. This work shows a boundary element formulation for static analysis of two parallel, elastically connected plates with an elastic layer in between. The plates are assumed to be represented by Kirchhoff plate model and the elastic layer is assumed to be a Winkler elastic foundation. Mathematical steps required to establish a BEM technique are adequately addressed: integral equations are derived using Betti’s reciprocal theorem, two fundamental solutions are obtained using Hӧrmander method; load domain integral is transformed into boundary integral, and algebraic system of double plate problem is formed and solved. Numerical examples associated with double plate problems having different mechanical properties boundary conditions, and load types are presented. The BEM results are compared with analytical solutions, showing satisfactory performance. In addition, the results show that both stiffness of the plates and spring constant of the elastic foundation play a relevant role on effect transmissibility within double plate system.